PENDIDIKAN MULTIKULTURAL PADA SEKOLAH BERBASIS AGAMA HINDU (STUDI KASUS DI SMA DWIJENDRA DENPASAR) - Marenita Putri, Ida Ayu Putu Eka; Punia, I Nengah; Krisna Aditya, I Gusti Ngurah Agung (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 1 No 02 (2021): JISSOROT, 2022)
Multicultural Education is a term that refers to the education of diversity. In Indonesia the implementation of multicultural education experienced several challenges, one of which occurred in schools affiliated with certain groups. SMA Dwijendra Denpasar is one example of a school based on Hinduism. this research used a qualitative approach with a type of descriptive-explanatory research taken through observation, interview, and document. The purpose of this research was to describe implementation of multicultural education in school based on Hinduism. Researcher found SMA Dwijendra Denpasar as school based on Hinduism can carry out the multicultural eduaction in their learning. Researcher also found during the implementation, SMA Dwijendra Denpasar faced some obstacle, but to overcome these obstacles, efforts are also made. Keywords: multicultural education, diversity, hinduism